تأثير الأحمال الجانبية على الجدران الحاملة في الأبنية الحجرية"" - طلال شرف (Tishreen University, 2018)
تم البحث بسلوك جدران القص البازلتية للمباني المتبقية من العصور الغابرة كبحث تجريبي، ومقاومتها للعوامل الطبيعية والحمولات الأفقية الناتجة عن الرياح والزلازل، للاستفادة منها في الحفاظ على المباني الحديثة والمرتبطة ببلاطات وجوائز كجدران قص أفقية على الارتفاع الطابقي في المناطق الحارة والباردة في القارة الأفريقية والأسيوية ومناطق أخرى مشابها لها على السواء، للاستعاضة بها عن جدران القص الخرسانية المسلحة والمعدنية التي تفقد مقاومتها للعوامل المذكورة أعلاه. لدى معاينة الأبنية وتوضع الشقوق الرأسية والمائلة الناتجة عن الحمولات الجانبية، تبين أن ظهور الشقوق يتعلق بصلادة مقطع الجدار وبمواصفات الحجر البازلتي وتصميم قاعدة الجدار [13]. تم البحث لتحديد المتانة ونفوذية الماء والمقاومة على الضغط والشد لعينات من الأحجار البازلتية المستخدمة في الأبنية الحجرية التاريخية ومواقع تواجدها بالطرائق المخبرية. تم حساب الشدة الزلزالية على واجهة البناء في مستوى البلاطات بالتوافق مع المواصفات والاشتراطات الدولية [1]، [10]، مع الاقتراح لطريقة حساب الجدار الحامل من الحجر البازلتي لبناء من عدة أدوار وقبو أخذين بعين الاعتبار المقاومة المميزة للبازلت حسب كثافته على الضغط والشد ومعامل الحجر البازلتي في العملية الحسابية. The behavior of the basaltic shear diaphragms of the remaining buildings of ancient times was investigated as experimental research,and its resistance to natural factors and horizontal loads resulting from wind and earthquakes,to take advantage of them in the maintenance of modern buildings,which are associated with floors and beams as horizontal shear diaphragmsIn the hot and cold areas of the African continent, Asia and other similar areas,to replace the reinforced concrete shear diaphragms,and metal shear diaphragms that lose their resistance to the above factors. When the buildings are inspected, the vertical and slanted slits resulting from the side loads are placed,it was found that the appearance of the cracks related to the hardness of the shear diaphragm section, the basalt stone specifications and the design of the shear diaphragm base [13].The research was conducted to determine the durability, water permeability and resistance to pressure and tensile strength of basalt stone samples used in historic stone buildings and their location in laboratory methods.Horizontal loads resulting from seismic intensity were determined on the front of the building at the tile level according to international requirements and specifications [1], [10].The method of calculating the basaltic shear diaphragms was applied by applying arithmetic to build a basalt stone from several floors and a basement, taking into account the characteristic resistance of basalt, depending on its density from pressure and stretching and basalt stone in calculating.